2013
DOI: 10.3390/ijms140713063
|View full text |Cite
|
Sign up to set email alerts
|

New Labdane-Type Diterpenoids and Anti-Inflammatory Constituents from Hedychium coronarium

Abstract: Four new labdane-type diterpenoids: hedychicoronarin (1), peroxycoronarin D (2), 7β-hydroxycalcaratarin A (3), and (E)-7β-hydroxy-6-oxo-labda-8(17),12-diene-15,16-dial (4), have been isolated from the rhizomes of Hedychium coronarium, together with 13 known compounds (5–17). The structures of these new compounds were determined through spectroscopic and MS analyses. Compounds 3, 5, 6, and 10 exhibited inhibition (IC50 values ≤4.52 μg/mL) of superoxide anion generation by human neutrophils in response to formyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Popular for its antiinflammatory activity, presence of 4 isolates in the plant namely 7-β-hydroxycalcaratarin A, calcaratarin A, coronarin A and E-labda-(17), 12-diene-15,16-dial were found in the plant possessing antiinflammatory potential which supports the traditional use of the plant in the prevention or treatment of various inflammatory diseases [94] . coronarin D has been shown to constrain the activation of the NF-kB pathway induced by different carcinogens and pro-inflammatory molecules and also debilitate the expression of constitutive NF-kB [95] .…”
Section: Roscoea Purpureamentioning
confidence: 59%
“…Popular for its antiinflammatory activity, presence of 4 isolates in the plant namely 7-β-hydroxycalcaratarin A, calcaratarin A, coronarin A and E-labda-(17), 12-diene-15,16-dial were found in the plant possessing antiinflammatory potential which supports the traditional use of the plant in the prevention or treatment of various inflammatory diseases [94] . coronarin D has been shown to constrain the activation of the NF-kB pathway induced by different carcinogens and pro-inflammatory molecules and also debilitate the expression of constitutive NF-kB [95] .…”
Section: Roscoea Purpureamentioning
confidence: 59%
“…The assay for measurement of superoxide anion generation was based on the SOD-inhibitable reduction of ferricytochrome c [ 19 , 20 ]. In brief, after supplementation with 0.5 mg/mL ferricytochrome c and 1 mM Ca 2+ , neutrophils (6 × 10 5 /mL) were equilibrated at 37 °C for 2 min and incubated with different concentrations (10–0.01 μg/mL) of compounds or DMSO (as control) for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Degranulation of azurophilic granules was determined by measuring elastase release as described previously [ 19 , 20 ]. Experiments were performed using MeO-Suc-Ala-Ala-Pro-Val- p -nitroanilide as the elastase substrate.…”
Section: Methodsmentioning
confidence: 99%
“…The phytochemical study of the rhizomes from Hedychium coronarium showed the presence of benzoyl eugenol along with the labdane diterpenes isocoronarin D and ethoxy coronarin D also. Hedychium coronarium afforded oils whose major constituents were β-pinene (20.0 %), linalool (15.8 %), α-pinene (10.1 %), 1,8-cineole (10.7 %) and α-terpineol (8.6 %) in the leaf while the root consists mainly of β-pinene (23.6 %), α-humulene (17.1 %), β-caryophyllene (13.0 %), α-pinene (6.9 %) and elemol (6.9 %) 15,16 . The volatile constituents of the various parts of H. coronarium from other parts of the world have been reported 17 .…”
Section: Phytochemical Characteristicsmentioning
confidence: 99%